1996
DOI: 10.1002/(sici)1097-4628(19961219)62:12<2169::aid-app20>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prevulcanization on the rheological behavior of natural rubber/styrene butadiene rubber latex blends

Abstract: SYNOPSISThe effect of prevulcanization on the rheological behavior of natural rubber (NR), styrene butadiene rubber (SBR) latices, and their blends was studied with special reference to shear rate, blend ratio, vulcanizing systems, prevulcanization time, and accelerator systems. The NR latex showed a sharp increase in viscosity with increase in prevulcanization time due to high extent of crosslinking. However, SBR latex showed marginal effect on viscosity with prevulcanization time due to its low dry rubber co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Drying of the prevulcanised latex produces a crosslinked film and, thus, physical properties of the final product can be controlled by the design of crosslink in particle during prevulcanisation. It was reported that the rate of prevulcanisation reaction depends on the vulcanisation systems, and the extent of prevulcanisation has a profound effect on the formation of the latex film [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 90%
“…Drying of the prevulcanised latex produces a crosslinked film and, thus, physical properties of the final product can be controlled by the design of crosslink in particle during prevulcanisation. It was reported that the rate of prevulcanisation reaction depends on the vulcanisation systems, and the extent of prevulcanisation has a profound effect on the formation of the latex film [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 90%
“…The articles made from pre-vulcanized latex are then completely vulcanized at relatively high temperatures which is associated with drying of the product. [74][75][76] The preparation of latex-MWCNT nanocomposites commences with either dry milling or ultrasonication of MWCNT. However, both methods may lead to the breakup of MWCNT imparting inferior properties to the resulting nanocomposite as a consequence of strong compression and shear forces of ball milling or high power of ultrasonicating.…”
Section: Preparation Of Xsbr Micro-and Nanocompositesmentioning
confidence: 99%
“…Moreover, the products fabricated from pre‐vulcanized latex could be prepared easily by dipping method and the shapes and functions could be controlled by modifying the mold. Generally, pre‐vulcanization of NR latex could be achieved by various approaches such as sulfur, peroxide, and irradiation vulcanization systems . Pre‐vulcanization using sulfur as crosslinking agents is the most important process due to its ease of handling, low operating cost, and producing product with superior mechanical properties and thermooxidative stability than others.…”
Section: Introductionmentioning
confidence: 99%